Modeling Pinus radiata D. Don growth and pasture production under different land uses and climate scenarios - Ferreiro-Domínguez, N.; Rigueiro-Rodríguez, A.; Mosquera-Losada, M. R. (Frontiers in Ecology and Evolution, 2022)
Yield-SAFE is a biophysical model to predict long-term production according to light and water availability in agricultural, forest and agroforestry systems. The Yield-SAFE model should be calibrated and validated for the highest number of tree species and crops to be used as a management tool that takes into account climate change. This study aimed to calibrate and validate the Yield-SAFE model for Pinus radiata D. Don and sown pasture (Dactylis glomerata L.) to estimate the production in 1) forest systems, 2) agricultural systems and 3) silvopastoral systems established in Galicia (NW Spain) under different conditions of climate: i) reference “current” climate from 1961 to 1990, ii) climate from 2021 to 2050 and ii) climate from 2051 to 2080. The Yield-SAFE model can now be used to assess the long-term productivity of Pinus radiata D. Don and Dactylis glomerata L. under different land uses and climate conditions. The Yield-SAFE model simulated similar tree and pasture growth in all scenarios of climate because the inter-annual variation of climate was small. However, tree growth estimated with the Yield-SAFE model was higher in the silvopastoral systems than in the forest systems, indicating that land use had more impact on land productivity than climate. Therefore, in regions such as Galicia, the Yield-SAFE model could be used as a tool to support the land use change in an agroforestry context, whilst also including climate scenarios which is considered a valuable solution to mitigate the effect of climate change.